Sufism, black and white : a critical edition of Kitāb al-Bayād ̣wa-l-Sawād of Abū l-Hạsan al-Sīrjānī (d. circa470/1077) - Al-Sīrjānī, Abū l-Hạsan. (Islamic History and Civilization, 2012)
This critical Arabic text edition of K. al-Bayāḍ wa-l-sawād min khaṣāʾiṣ ḥikam al-ʿibād fī naʿt al-murīd wa-l-murād (\'The Black and White in the Words of Wisdom by Bondsmen Describing the Seeker and the Mystic Quest\'), a substantial handbook of early Sufism by Abū l-Ḥasan ʿAlī born al-Ḥasan al-Sīrjānī (d. circa 470/1077), is based on three manuscripts and is introduced by a detailed analytical study of the author and his work. The work is written in the tone of a guiding Sufi master and collects the mystical tradition of early Sufis in the form of anecdotes and concise aphorisms to instill guiding wisdom into the hearts of aspiring Sufi adepts. K. al-Bayāḍ wa-l-sawād forms an integral part of Sufi literature and is an essential source for the intellectual history of Islam until the middle of the 5th/11th century.